Examining family and school factors as predictors of delinquency: a study of juvenile offenders, at risk students, and low risk students in Malaysia - Tan, Bee Piang (Tanjong Malim, 2019)
Examining family and school factors as predictors of delinquency: a study of juvenile offenders, at risk students, and low risk students in Malaysia by Tan, Bee Piang